Audit Report Lag Analysis: The Effect of the Financial Ratios of LQ-45 Companies for the Period 2021-2024 (International Journal of Economics and Management Research, 2025)
This study aims to analyze the effect of financial ratios, including profitability, solvency, and liquidity, on Audit Report Lag in companies listed on the LQ-45 index. The population in this study consists of all companies listed on the LQ-45 index on the Indonesia Stock Exchange (IDX) during the period of 2021–2024. The research sample consists of secondary data determined using purposive sampling techniques with the criteria of companies that are consistently listed on the LQ-45 index and publish audited annual financial reports during the observation period, resulting in 20 companies with a total of 80 observations. Profitability was measured using Return on Assets (ROA), solvency using Debt to Equity Ratio (DER), and liquidity using Current Ratio (CR). The data analysis technique used was Partial Least Square–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. The results showed that profitability, solvency, and liquidity partially had a significant effect on Audit Report Lag. In addition, simultaneously, the three financial ratios were proven to have a significant effect on Audit Report Lag. These findings indicate that a company's financial condition plays an important role in determining the length of the process of completing and submitting audited financial reports.